SUPERFICIAL VENOUS ANEURYSM OF THE HAND: Venous Aneurysm of the Hand - Mishwani, Brig Ahmad Hussian (Pakistan Armed Forces Medical Journal, 2010)
Venous aneurysm is dilatation of a localized segment of a vein. Superficial venous aneurysm of the upper extremities is a rare condition. Lipshutz and Rabwin first described it in1960 and since then only 19 cases have been published in literature1. To our knowledge no case has been reported from Pakistan so far. These may require treatment for cosmetic reason or complications